Animal Welfare and Human Ethics: A Personality Study - Konstanze Albrecht; Florentin Krämer; Nora Szech (Center for Economic Studies and ifo Institute (CESifo), 2017)
We revisit the long-standing question whether there is a relation between animal welfare and human ethics. Therefore, we elicit concern for animal welfare in an incentivized, direct, and real setup: Subjects choose between intensive farming versus organic living conditions for a hen. Guaranteeing organic living conditions is costly, but implies organic feed, access to daylight, and more space. We compare the interest in animal welfare with morally relevant dispositions in subjects, relying on well-established measures such as Machiavellianism scores and the Big 5 personality test. The data confirm a strong, positive relation between caring for animal welfare and moral dispositions.
Keywords: D01; D62; D69; 330; animal welfare; human ethics; experiment; sustainability